Exposure to imipenem/cilastatin causes nephrotoxicity and even urolithiasis in Wistar rats. (1st July 2018) - Tahri, Amal; Lahyani, Amina; Kallel, Rim; Ayadi, Fatma; Boudawara, Tahia; Sahnoun, Zouheir
Abstract: Imipenem/cilastatin is a broad-spectrum β-lactam antibiotic used to treat several bacterial infections. The present study was designed to validate the nephrotoxic effect of this drug in rats and to explore its potentional urolithiatic effect. Thirty two Wistar rats were randomly divided into four groups: three experimental groups treated with different imipenem/cilastatin dosages (30, 50 and 80 mg/kg/day) and a control group.The experimental groups were given intraperitoneal imipenem/cilastatin injections twice daily for 7 days, and the control group was given intraperitoneal vehicle NaCl 0.9% solution. Nephrotoxic effect of this antibiotic was assessed based on urine and plasma biochemistry, oxidative stress parameters, histopathological examination and infrared spectroscopy characterization. Imipenem/cilastatin administration resulted in alkaline urine, polyuria, crystalluria, raised plasma levels of urea, creatinine and uric acid, decreased contents of plasma gamma glutamyltranspeptidase and alkaline phosphatase, oxidative stress status, malpighian metaplasia as well as crystal deposition in kidneys and urinary tracts of Wistar rats. In addition, the precise nature of the calculi was identified, being formed by imipenem/cilastatin, thus confirming their iatrogenic origin. In conclusion, this study demonstrated through rat model that subacute exposure to imipenem/cilastatin may induce nephrotoxicity and increase the risk for developing kidney stones even at therapeutic dose levels in a dose-dependent manner.